Tributa????o, democracia e desenvolvimento: o tributo como garantidor da igualdade e da liberdade - Neiva, Leonardo Jos?? Feitosa (2015)
The aim of this work is clarify the relation among taxation, democracy and development. The main argument is that taxes may serve to strengthen the democracy as well as the social development process, when they are created or designed to safeguard the principles of equality and freedom. Some development theories claim that the necessary conditions for social development and democracy sustain one each other. Thus, the study begins with the explanation of these theories and so clarifying the construction of the main idea. After that, this work presents the fundamentals of democracy theory, since it is necessary to understand its core values and its essential institutions, in order to demonstrate that democracies can be strengthened. The study also analyzes how the tax theories of liberalism and social-democracy understand that the taxes should be set in order to safeguard the equality and freedom. These ideologies were responsible for inspiring the creation and development of tax systems of the developed countries, and they have very different understandings. Liberalism understands that tribute must protect, above all, the equitable distribution of the tax burden, economic liberty and the private property. Social-democracy, in turn, argues that taxation should promote the citizens well-being and ensure the smooth functioning of economy. Finally, the work analyzes the contemporary banking systems of the developed countries. Common standards are identified that form the features of the systems, and then, it is checked whether these standards strengthen or not the principles of equality and freedom. Nowadays it is observed that systems are in an equilibrium point located closest to the liberal ideal of taxation, and it is most appropriate to preserve the equality and freedom in order to strengthen democracy and promote development.